THE SYSTEM OF FINANCE AND TAXES: THE MAIN TOOL FOR THE DEVELOPMENT OF THE COUNTRY - Qurbanov Azimjon Xasanovich; Mansurov Javlonbek Jurabek o‘g‘li (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: The financial and tax system is an economic system of great importance in society. This system is an important tool for the development of the country. Our article will consist in providing our scientific and practical feedback on the details of the system of finance and taxes, the results of their positive development that leads to society, their importance in supporting development and the most important issues of handling them.